The importance of FcRn in neuro-immunotherapies: From IgG catabolism, FCGRT gene polymorphisms, IVIg dosing and efficiency to specific FcRn inhibitors - Dalakas, Marinos C.; Spaeth, Peter J. (Therapeutic advances in neurological disorders, 2021)
The neonatal Fc receptor (FcRn) binds endogenous IgG and protects it from lysosomal degradation by transporting it back to the cell surface to re-enter the circulation, extending the serum IgG life span. FcRn plays a role in the function of IVIg because the supraphysiological IgG levels derived from IVIg administrations saturate the FcRn allowing the endogenous IgG to be degraded, instead of being recycled, resulting in high levels of infused IgG ensuring IVIg efficiency. New data in myasthenia gravis patients suggest that the that the Variable Number of Tandem 3/2 (VNTR3/2) polymorphisms in FCGRT, the gene that encodes FcRn, may affect the duration of infused IgG in the circulation and IVIg effectiveness. This review addresses these implications in the context of whether the FCGRT genotype, by affecting the half-life of IVIg, may also play a role in up to 30% of patients with autoimmune neurological diseases, such as Guillain–Barré syndrome, CIDP or Multifocal Motor Neuropathy, who did not respond to IVIg in controlled trials. The concern is of practical significance because in such patient subsets super-high IVIg doses may be needed to achieve high IgG levels and ensure efficacy. Whether FCGRT polymorphisms affect the efficacy of other therapeutic monoclonal antibodies by influencing their distribution clearance and pharmacokinetics, explaining their variable effectiveness, is also addressed. Finally, the very promising effect of monoclonal antibodies that inhibit FcRn, such as efgartigimod, rozanolixizumab and nipocalimab, in treating antibody-mediated neurological diseases is discussed along with their efficacy in the IgG4 subclass of pathogenic antibodies and their role in the blood–brain barrier endothelium, that abundantly expresses FcRn.